Therapeutic Potential of Propolis Extract in Managing Hyperinflammation and Long COVID‐19: A Bioinformatics Study - Anshori, Isa; Marcius, Donny; Syaifie, Putri Hawa; Siregar, Khalish Arsy Al Khairy; Syakuran, Luqman Abdan; Jauhar, Muhammad Miftah; Arda, Adzani Gaisani; Shalannanda, Wervyan; Mardliyati, Etik (Chemistry & biodiversity, 2025)
ABSTRACT Hyperinflammation is a significant factor in long COVID, impacting over 65 million post‐COVID‐19 individuals globally. Herbal remedies, including propolis, show promise in reducing severity and pro‐inflammatory cytokines. However, the natural pharmacological role of propolis in COVID‐19 management remains underexplored. Employing network pharmacology and in silico techniques, we assessed propolis extract's potential in countering SARS‐CoV‐2‐induced inflammation. We identified 80 flavonoids via LC–MS/MS QTOF and employed 11 anti‐inflammatory drugs as references for inflammation target fishing. Utilizing in silico techniques encompassing target fishing, molecular docking, and dynamics, we examined propolis' effects. We identified 1105 gene targets connected to inflammation through multiple validated target predictors. By integrating SARS‐CoV‐2 DEGs from GSE147507 with these targets, we identify 25 inflammation‐COVID‐19‐associated propolis targets, including STAT1, NOS2, CFB, EIF2K2, NPY5R, and BTK. Enrichment analyses highlighted primary pharmacological pathways related to Epstein‐Barr virus infection and COVID‐19. Molecular docking validated isokaempferide, iristectorigenin B, 3′‐methoxypuerarin, cosmosiin, and baicalein‐7‐O‐β‐d‐glucopyranoside, which exhibited strong binding affinity and stability with relevant genes. Moreover, our findings indicate that propolis ligands could potentially suppress reactivation of Epstein‐Barr Virus infections in post‐COVID‐19 cases. However, this study has a limitation in that the concentration of each propolis compound has not been quantified. Therefore, further exploration of propolis compounds quantification and experimental validation are needed to support these findings.